Transformation of Masjid: empowerment of Muslims economy through e-halal one stop centre (E-HOSC) - Ahmad Dahlan, Abdul Rahman; Zakaria, Intan Munirah; Mohamed Azizan, Nour Tiara Natasha; Abdullah, Nur Isharra (Research Publish Journals, 2015)
Economy is one of the important tools in the upbringing of human’s civilization. Looking back at the Golden Age of Islam, Muslims merchants were all over the world not just for trading purposes but also to spread the beautiful teaching of Islam. During the reign of Caliph Harun al-Rashid (170-193 A.H.) the Muslim world experienced the best moment where each members of the society was taking part in the economic activities as they wanted to contribute to the society. Thus, it led to the level of almost no poverty at all (Ismail, 2012). History also portrayed that Prophet Muhammad sallahu’alaihiwasallam and many of the sahabah were successful businessmen. However, it seems the world has gone upside down where most of the Muslims nowadays have been left far behind and live in poverty and abused by others. Therefore, the role of Mosque need to be revised on the basis of Islam as a syumul religion which comprises all life segments including the economy or muamalat. e-Halal One Stop Centre (e-HOSC) is being proposed to help the Muslim entrepreneurs especially to those who are still searching for the best platform to market their products with zero cost and in the same time helping the consumers to find halal products from Muslim producers. This program is the extension of eHalal4All Program (Abdul Rahman Ahmad Dahlan et al, 2014), with the aim to enhance the economic and social well being of rural communities in Sabah, Malaysia. e-HOSC will be maintained and supervised by Masjid Negara (National Mosque) supported by Jabatan Kemajuan Islam Malaysia (JAKIM) and SME Corp as the centre and will be integrated with all mosques in Malaysia via Network-of-Mosques (NoM). Masjid Negara is being proposed as the administrator as one of its functions is to make a range of activities for Muslim community and it is an established organization where it has publication and multimedia unit which can be assigned to manage e-HOSC portal. Literature review and Business Model Canvas will be used as the methodology approach. Also, we would adapt the concept used by online marketplaces like Amazon.com or Mudah.my and leveraging on mobile apps to ensure the acceptance, reliability and efficiency of the program. This program is expected to enhance the Muslim entrepreneurs and increase their market shares and indirectly, people will be closer to the mosque and thus, proved the completeness of Islam as the way of life.